Public Finance Sustainability in Poland the Light of Fiscal Sustainability Indicators - Uryszek, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of the article is to assess the degree of sustainability of the public finance sector in Poland. Such a research goal is accompanied by the following research hypothesis: high values of primary deficits make it impossible to stabilize the level of public debt even in the long run. The analysis uses the concept of the so‑called fiscal sustainability indicators proposed, among others, by Buiter, Blanchard, Rudin and Smith. Reference was made to the Ponzi scheme in the context of the state solvency. The study used data from Eurostat and the Directorate General for Economic and Financial Affairs of the European Commission. The data come from the period 2001–2017. Forecasts for 2018 and 2019 were also used. The results for Poland were compared to the values for all EU countries.